2017
DOI: 10.1017/s0022377817000800
|View full text |Cite
|
Sign up to set email alerts
|

Toward laboratory torsional spine magnetic reconnection

Abstract: Magnetic reconnection is a fundamental energy conversion mechanism in nature. Major attempts to study this process in controlled settings on Earth have largely been limited to reproducing approximately two-dimensional (2-D) reconnection dynamics. Other experiments describing reconnection near three-dimensional null points are non-driven, and do not induce any of the 3-D modes of spine fan, torsional fan or torsional spine reconnection. In order to study these important 3-D modes observed in astrophysical plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 77 publications
(235 reference statements)
0
15
0
Order By: Relevance
“…Lundquist number S > 1, see § 3.2). Here, we investigate a well-studied plasma condition that is applied to satisfy such conditions in a unique configuration (Chesny et al 2017), including the feasibility for enabling reconnection, as shown by the computed plasma parameters and their resulting particle acceleration profiles. Of particular interest to the plasma physics community would be the exploration of plasma drifting into a 3-D null point region waiting for the plasma to envelope it and feasibly resulting in a moving reconnection site (Lukin & Linton 2011;Chesny et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lundquist number S > 1, see § 3.2). Here, we investigate a well-studied plasma condition that is applied to satisfy such conditions in a unique configuration (Chesny et al 2017), including the feasibility for enabling reconnection, as shown by the computed plasma parameters and their resulting particle acceleration profiles. Of particular interest to the plasma physics community would be the exploration of plasma drifting into a 3-D null point region waiting for the plasma to envelope it and feasibly resulting in a moving reconnection site (Lukin & Linton 2011;Chesny et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The initial study of Chesny et al (2017) described a feasible apparatus that achieved both of the previous conditions, but stopped short of demonstrating particle response to reconnection. Numerous authors (Dalla & Browning 2005Stanier, Browning & Dalla 2012;Hosseinpour, Mehdizade & Mohammadi 2014;Gascoyne 2015;Threlfall et al 2015;Pallister, Pontin & Wyper 2019) have employed a test particle approach to demonstrate relativistic particle acceleration in torsional reconnection under collisionless solar plasma conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Significant thrust is generated in the form of plasmoids (confined plasma objects in closed magnetic loops) when helicity is injected into a cylindrical vessel to induce magnetic reconnection. Existing space-proven plasma thrusters, including the ion thruster (Stuhlinger 1964;Choueiri 2009) and the Hall-effect thruster (Morozov et al 1972;Raitses, Smirnov & Fisch 2007), electrostatically accelerate ions to exhaust velocities v e of tens of kilometres per second to produce thrust. However, for space exploration to Mars and beyond, high-thrust electromagnetic propulsion with exhaust velocities of tens to hundreds of kilometres per second is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike existing plasma accelerators, the thrust is generated from the acceleration of bulk fluid due to continuous formation of reconnecting plasmoids in the magnetohydrodynamic (MHD) regime. Neither external pulsing nor rotating fields (Chesny et al 2017;Bathgate et al 2018) are required here for acceleration through reconnection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation